Muons in air showers at the Pierre Auger Observatory: Measurement of atmospheric production depth - Dova, María Teresa (2014)
The surface detector array of the Pierre Auger Observatory provides information about the longitudinal development of the muonic component of extensive air showers. Using the timing information from the flash analog-to-digital converter traces of surface detectors far from the shower core, it is possible to reconstruct a muon production depth distribution. We characterize the goodness of this reconstruction for zenith angles around 60° and different energies of the primary particle. From these distributions, we define Xμmax as the depth along the shower axis where the production of muons reaches maximum. We explore the potentiality of Xμmax as a useful observable to infer the mass composition of ultrahigh-energy cosmic rays. Likewise, we assess its ability to constrain hadronic interaction models.